Global Research Trends in the Latarjet Procedure: A Bibliometric and Visualized Study - Visconti-Lopez, Fabriccio J. (2022)
Background and Objectives: Latarjet is among the procedures indicated to treat shoulder instability, producing excellent results, including low instability rates and high patient satisfaction. The aim of this study was to report the characteristics of scientific articles that address the subject of the Latarjet procedure through the use of bibliometric analysis. Materials and Methods: Bibliographic searches were performed for original articles published in journals indexed by the Web of Science database until 2021, with no language restrictions. Results: A total of 668 articles published in 87 journals were included. The first publication was in 1981; the most registered publications were in 2018 and 2021 (89 articles), with an annual percentage growth rate of 11.9. Provencher MT was the author with the most published articles, and the institutional affiliation with the most original articles was the Steadman Philippon Research Institute. The most cited article was a study by Burkhart and Beer, and the scientific journal with the most publications on the subject was the Journal of Shoulder and Elbow Surgery. Most published studies included keywords such as dislocation, instability, and meta-analysis. Conclusion: There has been a sustained increase in original articles on the Latarjet procedure. However, the greatest growth in articles has occurred during the last decade, demonstrating the considerable interest among the world scientific community.